2021
DOI: 10.1177/21514593211055889
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Full Weight-Bearing Versus Partial Weight-Bearing After Plate Fixation of Distal Femur Fractures in Elderly Patients. A Randomized Controlled Trial

Abstract: Introduction After surgery for distal femur fractures in elderly patients, weight-bearing is commonly restricted. Immediate non-restrictive weight-bearing might have beneficial effects. There are no randomized studies on the topic. The purpose of this study was to compare the functional outcome between immediate full weight-bearing (FWB) as tolerated and partial weight-bearing (PWB) during the first 8 weeks following plate fixation of distal femur fractures in elderly patients. Methods Patients aged 65 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
0
10
0
2
Order By: Relevance
“…According to Keenan et al, immediate weight bearing had no noticeable effect on reoperation risks in patients with lateral locked plate fixation of periprosthetic distal femoral fractures, although these apply to those older patients and not patients with histories of long term glucocorticoid use (4). No differences in functional outcomes were noted in a randomized control study by Paulsson et al (9). In cases of those with obesity, postoperative complications of THP are noticeably increased, which should be a consideration factor when introducing weight bearing exercises in rehabilitation (7).…”
Section: Discussionmentioning
confidence: 98%
“…According to Keenan et al, immediate weight bearing had no noticeable effect on reoperation risks in patients with lateral locked plate fixation of periprosthetic distal femoral fractures, although these apply to those older patients and not patients with histories of long term glucocorticoid use (4). No differences in functional outcomes were noted in a randomized control study by Paulsson et al (9). In cases of those with obesity, postoperative complications of THP are noticeably increased, which should be a consideration factor when introducing weight bearing exercises in rehabilitation (7).…”
Section: Discussionmentioning
confidence: 98%
“…However, several small series of patients with distal femur fracture have demonstrated similar reoperation rates for restricted and full weight-bearing patients. 4 , 14 However, geriatric nonhip fractures continue to have higher rates of restricted weight-bearing than geriatric hip fractures. 15 The findings of this study further highlight the hesitancy to allow distal femur fractures to immediately weight-bear after surgical fixation.…”
Section: Discussionmentioning
confidence: 99%
“…This study evaluated previously unpublished secondary outcomes from a randomized controlled trial investigating the influence of weight-bearing regimens on patient-reported outcomes following surgically treated elderly patients with DFFs. 29 Between January 2013 and June 2016, 32 patients were allocated to immediate full weight-bearing (FWB) or partial weight-bearing (PWB) regimens for 8 weeks.…”
Section: Methodsmentioning
confidence: 99%